Latchup-free ESD protection design with complementary substrate-triggered SCR devices. - Ming-Dou Ker (IEEE Journal of solid state circuits)
The turn-on mechanism of silicon-controlled rectifier (SCR) devices is essentially a current triggering event. While a current is applied to the base or substrate of an SCR device, it can be quickly triggered on into its latching state. In this paper, latchup-free electrostatic discharge (ESD) protection circuits, which are combined with the substrate-triggered technique and an SCR device, are proposed. A complementary circuit style with the substrate-triggered SCR device is designed to discharge both the pad-to-VSS and pad-to-VDD ESD stresses. The novel complementary substrate-triggered SCR devices have the advantages of controllable switching voltage, adjustable holding voltage, faster turn-on speed, and compatible to general CMOS process without extra process modification such as the silicide-blocking mask and ESD implantation. The total holding voltage of the substrate-triggered SCR device can be linearly increased by adding the stacked diode string to avoid the transient-induced latchup issue in the ESD protection circuits. The on-chip ESD protection circuits designed with the proposed complementary substrate-triggered SCR devices and stacked diode string for the input/output pad and power pad have been successfully verified in a 0.25-μm salicided CMOS process with the human body model (machine model) ESD level of ∼7.25 kV (500 V) in a small layout area.